The Use of Fruit Yeast as a Substitute for Instant Yeast in Sweet Bread Products - Thawerattanon, Nuttanun; Poolcharoensil, Noppamas; Uthai, Narissara; Wongtom, Rungtip; Kaikaw, Doungtip; Yampuang, Racharat (Journal of Food Health and Bioenvironmental Science, 2023)
This study aimed to solve the problem of fruit wastage through the following objectives: (1) create usage for food waste materials from the food industry, (2) study the process of yeast fermentation from fruits and (3) study the physical properties of sweet bread. The ability to form yeasts was studied using a total soluble solid (TSS) (°Brix). TSS decreased, indicating the amount of yeasts formed. Fermented sugarcane contained more yeast than fermented apple based on the TSS of sugarcane and apple fermented broths on the third day, which decreased by 50.85% and 34.5% (p ≤ 0.05), respectively, while instant yeast decreased by 79.2%. The culture broth yeast was used as a substitute for instant yeast in sweet bread products. The physical properties of the bread were studied by volume, specific volume, density and texture profile analysis. The use of yeast from sugarcane and apple had a decreased volume that resulted in a decrease in specific volume by an average of 13.29% and 28.33%, respectively and had more density and more rigid texture than instant yeast (p ≤ 0.05). Thus, consumers who are allergic to instant yeast powder now have an alternative with the bread produced from fermented fruit yeast.